1468 - Susana Münch Miranda (The Global History of Portugal, 2021)
This paper develops the concept of graduated involution to explain how summer holidays have been reconstituted from leisure time into an educational arena for Chinese families under conditions of compressed modernity. Based on qualitative data from 32 households in Shanghai, including interviews and child self-recordings, we analyze how temporal acceleration, spatial reconfiguration, and institutional gradients interact to shape children's everyday lives. We show that educational responsibility has increasingly been transferred from the state to families through hukou-based entitlements and graduated polices such as school catchment areas and "Jifen"-or points for different categories of urban citizenship, producing stratified family responses and uneven childhood trajectories. Summer holidays thus function as a microcosm of compressed modernity's contradictions, where rapid social transformation coexists with persistent familialism. The analysis advances debates on welfare retrenchment, life-course inequality, and the governance of childhood beyond formal institutions.